Decreased HHV-6 IgG in Alzheimer’s Disease - Westman, Gabriel; Blomberg, Jonas; Yun, Zhibing; Lannfelt, Lars; Ingelsson, Martin; Eriksson, Britt-Marie (Frontiers in Neurology, 2017)
Human herpesviruses have previously been implicated in the pathogenesis of Alzheimer's disease (AD) but whether they are causal, facilitating or confounding factors is yet to be established. A total of 50 AD subjects and 52 non-demented (ND) controls were analysed in a multiplex assay for IgG reactivity towards HSV, VZV, CMV and HHV-6. The HHV-6 IgG reactivity was significantly lower in AD subjects compared to non-demented controls, whereas there were no differences in HSV, VZV or CMV antibody levels between the groups. Analysis of peripheral blood mononuclear cells with a subtype specific HHV-6 PCR revealed no signs of reactivation, as AD and ND subjects presented with comparable HHV-6 DNA levels in PBMCs and all positive samples were of subtype B. Whether HHV-6 is a factor in AD remains to be elucidated in future studies.